Publications of Mykolas Biržiška in Vilnius press at the beginning of the 20th century: features of the intellectual biography - Kvietkauskas, Mindaugas (Knygotyra, 2006)
Mykolas Biržiška (1882–1962) was a prominent Lithuanian scholar and politician, a signatory of the Act of Independence (1918), a member of the Lithuanian Council (1917–1920), director of the first Lithuanian Gymnasium of Vytautas the Great in Vilnius (1915–1922), and professor and rector of Kaunas and Vilnius universities.This article deals with his early journalistic activities and editorship in the press in Vilnius before the outbreak of the First World War, and seeks to analyze the formation of his intellectual and political attitudes. In 1905, being a member of the Party of Lithuanian Social Democrats, Biržiška began his journalistic career in the socialist press. In 1906 he edited a party newspaper "Echo" in Polish, where his specific interest in cooperation between different nationalities first became vivid.At the same time he began contributing to the liberal and antinationalist newspaper of the Polish krajovtsy movement "Gazeta Wilenska" (edited by Michał Romer), which argued for the political equality and tolerant cultural coexistence of all the national groups in Lithuania. After the closure of "Gazeta Wilenska," Biržiška in 1907–1908 cooperated with another liberal daily in Russian, "Severo-Zapadnyj Golos."Writing in three languages and simultaneously contributing to Lithuanian, Polish, and Russian press, Biržiška exercised a specific role as a publicist and mediator between different cultural groups in the multinational city. Professional analysis of national conflicts, the principles of cultural tolerance, and liberal antinationalist outlooks became the dominant features of his trilingual journalistic texts.Consequently, Biržiška sought to realize these intellectual attitudes while working at the Lithuanian daily "Vilniaus žinios" in 1908 and especially editing the journal "Visuomenė" (1910–1911) for the Lithuanian leftist intelligentsia. Biržiška's journalistic activities and early intellectual biography carried features of specific cultural liberalism that was characteristic of the entire group of multinational intelligentsia in Vilnius before the First World War (Michał Romer, Tadeusz Wróblewski, Anton and Ivan Luckievich, Uriah Katzenelenbogen, and others).
Keywords: -